Pelaksanaan Program Gerakan Nasional Pendidikan Anak Usia Dini di Kabupaten Banyumas (Evaluasi Program Berdasarkan Goal Oriented Model) - Fauzi Fauzi (Jurnal Penelitian Agama, 2014)
Abstract: This article presents the results of an evaluative study on theimplementation of a national movement for early childhood education (Paudisasimovement) in Banyumas district. The selected program evaluation model that isgoal oriented models. The study results showed that the general implementation ofPaudisasi movement in Banyumas district has led to the achievement of the setprogram standards. Yet still found lest than optimal program on every aspect of theprogram is based on criteria or indicators specified program. Necessary to optimizethe implementation of a national movement programs for early childhood educationin a more creative, substantive and qualitative.Keywords: evaluation of the program, a national movement for early childhoodeducation. Abstrak: Artikel ini memaparkan hasil kajian evaluatif atas pelaksanaangerakan nasional pendidikan anak usia dini (gerakan Paudisasi) di kabupatenBanyumas. Model evaluasi program yang dipilih yakni goal oriented model. Hasilkajian menunjukan bahwa secara umum pelaksanaan gerakan Paudisasi dikabupaten Banyumas telah mengarah pada upaya pencapaian standar programyang ditetapkan. Namun demikian masih ditemukan kekurangoptimalanpelaksanaan program pada setiap aspek program berdasarkan kriteria atauindikator program yang ditetapkan. Diperlukan optimalisasi implementasi programgerakan nasional pendidikan anak usia dini secara lebih kreatif, substantif, dankualitatif.Kata Kunci: evaluasi program, gerakan nasional pendidikan anak usia dini.